Dangerous men - Becker, Geoffrey, 1959- (Pitt Drue Heinz Lit Prize Ser., 1995)
Eleven stories on violence. In the title story, teenagers in Boston contemplate gay bashing, Taxes is onthe reaction of a youth whose brother wants to rob hisemployer, and in Magister Ludi a girl turns the tables onher pursuer.